2017
DOI: 10.1016/j.epsl.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of titanite crystallisation on Eu and Ce anomalies in zircon and its implications for the assessment of porphyry Cu deposit fertility

Abstract: The redox sensitivity of Ce and Eu anomalies in zircon has been clearly demonstrated by experimental studies, and these may represent an important tool in the exploration for porphyry Cu deposits which are thought to be derived from oxidised magmas. These deposits are significant because they are the source of much of the world's copper and almost all of the molybdenum and rhenium, key elements in many modern technologies. However, Ce and Eu anomalies in zircon are also affected by the co-crystallisation of RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
101
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(105 citation statements)
references
References 47 publications
4
101
0
Order By: Relevance
“…Furthermore, zircon formed in melts derived from enriched versus depleted mantle shows differences in Nb content, such that zircon grains in depleted mid-oceanic ridge basalt (MORB) settings on average exhibit at least an order of magnitude lower Nb/Yb ratio than zircon from plume-influenced ocean island or continental flood basalt (Grimes et al, 2015). Zircon Ce and Eu anomalies have been shown to vary as a function of magma oxidation state and the plagioclase sequestration, which may be leveraged to discriminate between geodynamic growth environments (Burnham & Berry, 2012;Loader et al, 2017;Trail et al, 2012). Zircon Ce and Eu anomalies have been shown to vary as a function of magma oxidation state and the plagioclase sequestration, which may be leveraged to discriminate between geodynamic growth environments (Burnham & Berry, 2012;Loader et al, 2017;Trail et al, 2012).…”
Section: Zircon U-pb (U-th)/he and Trace Element Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, zircon formed in melts derived from enriched versus depleted mantle shows differences in Nb content, such that zircon grains in depleted mid-oceanic ridge basalt (MORB) settings on average exhibit at least an order of magnitude lower Nb/Yb ratio than zircon from plume-influenced ocean island or continental flood basalt (Grimes et al, 2015). Zircon Ce and Eu anomalies have been shown to vary as a function of magma oxidation state and the plagioclase sequestration, which may be leveraged to discriminate between geodynamic growth environments (Burnham & Berry, 2012;Loader et al, 2017;Trail et al, 2012). Zircon Ce and Eu anomalies have been shown to vary as a function of magma oxidation state and the plagioclase sequestration, which may be leveraged to discriminate between geodynamic growth environments (Burnham & Berry, 2012;Loader et al, 2017;Trail et al, 2012).…”
Section: Zircon U-pb (U-th)/he and Trace Element Analysismentioning
confidence: 99%
“…Progressive melt fractionation is also recorded in zircon as fluid mobile incompatible elements (e.g., LILEs, LREEs, and U) preferentially mobilize and decouple from fluid immobile high field strength elements (e.g., Nb, Y, and HREE). Zircon Ce and Eu anomalies have been shown to vary as a function of magma oxidation state and the plagioclase sequestration, which may be leveraged to discriminate between geodynamic growth environments (Burnham & Berry, 2012;Loader et al, 2017;Trail et al, 2012). Oxidizing conditions in subduction zones tend to promote higher Ce content in zircon due to greater compatibility of Ce 4+ than Ce 3+ (Burnham & Berry, 2014).…”
Section: Zircon U-pb (U-th)/he and Trace Element Analysismentioning
confidence: 99%
“…Zircons from magmatic rocks closely associated with mineralization have been shown to have high values of Ce 4+ /Ce 3+ and Eu/Eu*, with moderately elevated Ce/Ce* ( Fig. 6; see Loader et al, 2017), ascribed by most authors to oxidizing conditions at the time of crystallization (e.g. Dilles et al, 2015;Shen et al, 2015;Lu et al, 2016).…”
Section: Zirconmentioning
confidence: 99%
“…It was recommended that only high-Ta zircons (>0.2 ppm Ta) should be used to test for magmatic redox because these are not likely to have had their chemistry modified by titanite crystallization. Ce/Ce* may be unaffected but is difficult to determine accurately; Loader et al (2017) proposed the use of the formulation Ce* = Nd N 2 /Sm N to estimate Ce* in the absence of precise analytical data for La and/or Pr. A lot of overlap exists between barren and fertile magmas in terms of Ce/Ce* but values above ~100 are only rarely seen in barren suites and, when combined with robust Eu/Eu* values above 0.4 (Fig.…”
Section: Zirconmentioning
confidence: 99%
“…Furthermore, Loader et al (2017) demonstrated that titanite crystallization can have a major effect on Eu anomalies. It was recommended that only high-Ta zircons (>0.2 ppm Ta) should be used to test for magmatic redox because these are not likely to have had their chemistry modified by titanite crystallization.…”
Section: Zirconmentioning
confidence: 99%